2008
DOI: 10.1590/s0080-62342008000300022
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura organizacional do serviço de enfermagem: reflexões sobre a influência do poder e da cultura organizacional

Abstract: RESUMENEste artículo analiza cómo la cultura y el poder influyen en la estructura organizacional del servicio de enfermería en un hospital-escuela. Basados en la necesidad de protocolizar los procedimientos de enfermería, por parte de la administración general del hospital, se diseñó la estructura organizacional (organigrama) del Servicio de Enfermería. De esta forma fue evidenciado el interés de los enfermeros-jefes por ampliar el poder, fortaleciendo el sector de enfermería dentro del ámbito institucional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
0
10
1
13
Order By: Relevance
“…The complexity of the hospital and conflicting interests have led to new ways to manage, and the need to seek theoretical frameworks concerning micropolitics in the hospital. 8 In the classical management approach, employees do not participate in the decision process; they receive orders after decisions are made by the administrative leadership. 9 In current management models, called participatory, democratic, decentralized or shared management models, the decision must be a multidisciplinary process, integrating the whole team and distributing authority and power.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the hospital and conflicting interests have led to new ways to manage, and the need to seek theoretical frameworks concerning micropolitics in the hospital. 8 In the classical management approach, employees do not participate in the decision process; they receive orders after decisions are made by the administrative leadership. 9 In current management models, called participatory, democratic, decentralized or shared management models, the decision must be a multidisciplinary process, integrating the whole team and distributing authority and power.…”
Section: -3mentioning
confidence: 99%
“…7 Also, when the factors that influence the leadership styles are studied, individual manager characteristics are mainly emphasized, and some organizational issues that can affect management are not wells explored. 8 It is therefore necessary to determines which cultural characteristics influence each management style, because both must be compatible. 7,13 From this context, the aim of this integrative literature review is to identify and analyze the existing scientific literature on the influence of organizational culture on the viability of participatory management in healthcare organizations.…”
mentioning
confidence: 99%
“…The identification of these structures, which are present in all health services, make it easier for newly graduates to develop their activities in planning and developing more flexible and more visible actions (16) .…”
Section: Team Leadershipmentioning
confidence: 99%
“…A study about communication between nursing leaders and subordinates identified the following main conflicts in the communication process: lack of compliments from immediate superior to nurses, lack of honesty in interpersonal relations, lack of constructive criticism on nurses' professional performance, communication problems with other areas, non-welcoming of nurses' opinions and lack of acknowledgement of nursing work (8) . Another problem refers to the centralization of the decision process in nursing management, which obstructs the communication flow and delays the decision process, causes information distortions, hampering agility and the work process in practice (9) .…”
Section: Introductionmentioning
confidence: 99%